Biosynthesized Gold, Silver, Palladium, Platinum, Copper, and Other Transition Metal Nanoparticles - Piotr Roszczenko; Olga Klaudia Szewczyk; Robert Czarnomysy; Krzysztof Bielawski; Anna Bielawska (MDPI AG, 2022)
Nanomedicine is a potential provider of novel therapeutic and diagnostic routes of treatment. Considering the development of multidrug resistance in pathogenic bacteria and the commonness of cancer, novel approaches are being sought for the safe and efficient synthesis of new nanoparticles, which have multifaceted applications in medicine. Unfortunately, the chemical synthesis of nanoparticles raises justified environmental concerns. A significant problem in their widespread use is also the toxicity of compounds that maintain nanoparticle stability, which significantly limits their clinical use. An opportunity for their more extensive application is the utilization of plants, fungi, and bacteria for nanoparticle biosynthesis. Extracts from natural sources can reduce metal ions in nanoparticles and stabilize them with non-toxic extract components.